Macraucheniidae and Proterotheriidae (Mammalia, Litopterna) from Quebrada Fiera (Late Oligocene), Mendoza Province, Argentina - Schmidt, Gabriela Ines (2019)
In this contribution we present new specimens of Litopterna recovered during the last decade in Quebrada Fiera (Mendoza Province, Argentina), whose fossiliferous sediments, currently recognized as the base of Agua de la Piedra Formation, are assignable to Late Oligocene (Deseadan South American Land Mammal Age). Two remains mentioned in the first publication on this locality were neither detailed nor described, and they have not been located in the corresponding repository. The new material consists of postcranial fragmentary remains (astragali, calcaneum, and metapodials) of Macraucheniidae (Cramaucheniinae) and an incomplete upper molar (M3) of Proterotheriidae (Proterotheriinae). These few remains of litopterns contrast with the abundance of notoungulates at Quebrada Fiera. A comparative study was carried out with material from Patagonia (Argentina) and taxa recorded in Bolivia and Peru for the same temporal interval. The specimens of Cramaucheniinae are assigned to Coniopternium andinum and the molar of Proterotheriinae to cf. Lambdaconus suinus. This contribution allows us to extend the geographical range of Coniopternium, filling the gap between the Patagonian and lower latitude localities (Bolivia and Peru) in which this genus was found. The record of L. suinus in Quebrada Fiera expands the geographical range of this species outside from Patagonia.